Nano-scale charge trapping memory based on two-dimensional conjugated microporous polymer - Ayman Rezk; Md. Hasan Raza Ansari; Kayaramkodath Chandran Ranjeesh; Safa Gaber; Dayanand Kumar; Areej Merhi; Bilal R. Kaafarani; Mohamed Ben Hassine; Nazek El-Atab; Dinesh Shetty; Ammar Nayfeh (Scientific Reports, 2023)
Abstract There is a growing interest in new semiconductor nanostructures for future high-density high-performance flexible electronic devices. Two-dimensional conjugated microporous polymers (2D-CMPs) are promising candidates because of their inherent optoelectronic properties. Here, we are reporting a novel donor–acceptor type 2D-CMP based on Pyrene and Isoindigo (PI) for a potential nano-scale charge-trapping memory application. We exfoliated the PI polymer into ~ 2.5 nm thick nanoparticles (NPs) and fabricated a Metal–Insulator–Semiconductor (MIS) device with PI–NPs embedded in the insulator. Conductive AFM (cAFM) is used to examine the confinement mechanism as well as the local charge injection process, where ultrathin high-κ alumina supplied the energy barrier for confining the charge carrier transport. We have achieved a reproducible on-and-off state and a wide memory window (ΔV) of 1.5 V at a relatively small reading current. The device displays a low operation voltage (V < 1 V), with good retention (104 s), and endurance (103 cycles). Furthermore, a theoretical analysis is developed to affirm the measured charge carriers’ transport and entrapment mechanisms through and within the fabricated MIS structures. The PI–NPs act as a nanoscale floating gate in the MIS-based memory with deep trapping sites for the charged carriers. Moreover, our results demonstrate that the synthesized 2D-CMP can be promising for future low-power high-density memory applications.